Evaluation of the cytotoxicity of cigarette smoke total particulate matter using three in vitro assays and two types of cells. (May 2013) - Li, Xiang; Peng, Bin; Nie, Cong; Shang, Pingping; Liu, Huimin
Abstract In vitro cytotoxicity assays can be used to evaluate potential toxicological effects of tobacco products. Total particulate matter (TPM) from mainstream cigarette smoke trapped by a Cambridge filter is used widely for biological evaluation of smoke. This study compared neutral red uptake (NRU), lactate dehydrogenase (LDH) activity and WST-1 assays for assessing the cytotoxicity of TPM, and evaluated the sensitivity of Chinese hamster ovary (CHO) cells and human lung adenocarcinoma epithelial cell line (A549 cells) to TPM-induced cytotoxic effects. The results indicate that NRU and WST-1 assays are preferable to LDH activity assay for assessing the TPM-induced cytotoxicity, and NRU assay might be more sensitive than WST-1 assay. The cytotoxicity of 3R4F reference cigarettes and two commercial brands of cigarettes were tested by NRU assay in CHO and A549 cells. The results showed that EC50 values in CHO cells treated with TPM were lower than EC50 values in A549 cells, indicating CHO cells are more sensitive to TPM-induced cytotoxic effects than A549 cells.